Status quo, problem and promotion suggestions of 5G application in industrial field - Mengzhe ZHANG; Yijun XIA (Dianxin kexue)
The great value of 5G is to support high-quality development of the real economy.Based on the status quo and bottleneck problem of 5G application in the industrial field, the “classified and targeted” development path was built.According to characteristics of typical 5G application scenarios in the industrial field, they were divided into 3 types—leading, exploring and lagging, and corresponding promotion suggestions were proposed.